The relationship between the factors influencing the students' choice of nursing as a career and their academic performance in the college - Estember, Cristina Mae H.; Eva, Hazel B.; Garcia, Genevieve A.; Garcia, Mae Fairy S. (Manila College of Nursing, University of the Philippines Manila, 1995)
"Nursing entails a love of ministering to those in need, a quickness to observe symptoms, a gentle touch, a sympathetic nature, and a love of nursing work for the very work's sake...". If helping others is the fundamental activity of nurses, then it is important to determine if this is a major consideration in deciding to take up Nursing. It is also interesting to see if these factors influencing the students choice of Nursing as a career have an effect on their academic performance. This study was done to determine the following: (1) the factors which influenced the students' choice of Nursing as a career; (2) the academic performance of the students during the last three semesters; (3) the presence of a relationship between the factors influencing the students' choice of Nursing as a career and their academic performance. The study showed that there is no significant relationship between the factors influencing the choice of Nursing as a career and the students' academic performance in the college. In fact, students who were forced by circumstances to take up Nursing performed better than those who took up Nursing as a personal choice.
Includes bibliographies
A research paper presented to Prof. Cecilia M. Laurente in partial fulfillment of the requirements for the course Nursing Research (N-199)
Keywords: Nursing -- Research